The last ever after - Chainani, Soman; Bruno, Iacopo (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
The forces of evil want to take over and make Sophie their queen, but Tedros and her former friend Agatha try to stop them.
"Includes: a deleted chapter from Book One, a first look at The ever never handbooks"--Front cover.
Kirkus Review
Kirkus Review, July 2015
6.2
5-8
5-8
Keywords: Best friends -- Juvenile fiction; Good and evil -- Juvenile fiction; Schools -- Juvenile fiction; Best friends -- Fiction; Good and evil -- Fiction; Schools -- Fiction; Friendship -- Fiction; Good and evil -- Fiction; School stories; Fantastic fiction